Noncontrast free-breathing respiratory self-navigated coronary artery cardiovascular magnetic resonance angiography at 3 T using lipid insensitive binomial off-resonant excitation (LIBRE) - Jessica A. M. Bastiaansen (Journal of Cardiovascular Magnetic Resonance, 2019)
Abstract Background Robust and homogeneous lipid suppression is mandatory for coronary artery cardiovascular magnetic resonance (CMR) imaging since the coronary arteries are commonly embedded in epicardial fat. However, effective large volume lipid suppression becomes more challenging when performing radial whole-heart coronary artery CMR for respiratory self-navigation and the problem may even be exacerbated at increasing magnetic field strengths. Incomplete fat suppression not only hinders a correct visualization of the coronary vessels and generates image artifacts, but may also affect advanced motion correction methods. The aim of this study was to evaluate a recently reported lipid insensitive CMR method when applied to a noncontrast self-navigated coronary artery CMR acquisitions at 3 T, and to compare it to more conventional fat suppression techniques. Methods Lipid insensitive binomial off resonant excitation (LIBRE) radiofrequency excitation pulses were included into a self-navigated 3D radial GRE coronary artery CMR sequence at 3 T. LIBRE was compared against a conventional CHESS fat saturation (FS) and a binomial 1–180°-1 water excitation (WE) pulse. First, fat suppression of all techniques was numerically characterized using Matlab and experimentally validated in phantoms and in legs of human volunteers. Subsequently, free-breathing self-navigated coronary artery CMR was performed using the LIBRE pulse as well as FS and WE in ten healthy subjects. Myocardial, arterial and chest fat signal-to-noise ratios (SNR), as well as coronary vessel conspicuity were quantitatively compared among those scans. Results The results obtained in the simulations were confirmed by the experimental validations as LIBRE enabled near complete fat suppression for 3D radial imaging in vitro and in vivo. For self-navigated whole-heart coronary artery CMR at 3 T, fat SNR was significantly attenuated using LIBRE compared with conventional FS. LIBRE increased the right coronary artery (RCA) vessel sharpness significantly (37 ± 9% (LIBRE) vs. 29 ± 8% (FS) and 30 ± 8% (WE), both p < 0.05) and led to a significant increase in the measured RCA vessel length to (83 ± 31 mm (LIBRE) vs. 56 ± 12 mm (FS) and 59 ± 27 (WE) p < 0.05). Conclusions Applied to a respiratory self-navigated noncontrast 3D radial whole-heart sequence, LIBRE enables robust large volume fat suppression and significantly improves coronary artery image quality at 3 T compared to the use of conventional FS and WE.